Antioxidant Effects of Temulawak and Black Cumin Honey in Stunted Children: A Study in Cirebon - Siti Pandawangi TW; Akrom Akrom; Nurkhasanah Nurkhasanah; Ahmad Azrul Zuniarto (Journal of Public Health and Pharmacy)
Introduction: The imbalance between the production of free radicals and the antioxidant defense system in the body will cause the body to experience oxidative stress. This can be caused by chronic malnutrition. In children, this condition causes growth and development failure called stunting. Honey, temulawak and black cumin are herbs with high antioxidant content, formulated in one preparation to test its effectiveness. The purpose of the study was to determine specific descriptions experienced by stunted children and to test the antioxidant effectiveness of preparation temulawak-black cumin honey.